A history in fragments: Europe in the Twentieth Century - Vinen, Richard (Abacus, 2002)
The problem with the history of twentieth-century Europe is that we all think we know it. The great stories of the century-the two world wars, the rise and fall of Nazism and Communism-seem self-evident in their importance. But behind the politics and the ideologies lies another history: the history of forces that shaped the lives of individual Europeans... and the lives of men and women around the world. (Americans need only think of the way that the history of Europe has shaped the flow ofimmigrants to the U.S. and thereby altered our nation's history.)Richard Vinen contends that there is no single history that encompasses the experience of the century, but rather a multiplicity of different, interlocking histories-stories not only of politics and military movements, but also of culture, religion, sex, and demographics, related here with an unmatched eye for the telling detail and spiced with memorable anecdotes. As the Sunday Telegraph put it: Vinen moves effortlessly from social and economic issues to politics, from ideology to military history. . . . The writing is lively, the enthusiasm infectious, and the gift for bold, epigrammatic summary genuinely impressive." A canvas encompassing both the broad and the particular, this is a major work of history-and history writing at its best."